(untitled) (Research, Society and Development, 2023)
Periodontitis has been identified as a systemic inflammatory stimulus, with a potential risk of occurrence or worsening of several systemic conditions. Objective: To evaluate the association between periodontitis and prostate diseases. Methodology: This narrative review included cross-sectional and longitudinal studies, clinical trials and systematic reviews, in English, indexed in PubMed/Medline and Lilacs. The combined descriptors “periodontitis”, “periodontal disease”, “prostatitis”, “benign hyperplasia” and “prostate cancer” were used. Clinical cases, case reports and opinion articles were excluded. A screening was carried out by title followed by reading of the abstracts. Verified in relation to the topic, the articles were read in full by a single researcher. Results: Observational studies related to the association between periodontitis and prostate diseases (OR 1.41), cohorts indicate a risk of prostate diseases (RR=2.621) in individuals with untreated periodontitis and Meta-Analyses report a risk of around 1.17 in patients with periodontitis (RR=1.17; 95% CI 1.07-1.27; p=0.001). The possibility for this association is the immunological inflammatory relationship between periodontitis and prostate diseases. Periodontal pathogens can spread, reach the prostate and penetrate the intraepithelial tissue, causing histological changes in the organ. Conclusion: The studies are diverse and the evidence is limited, however, they point to a possible association between periodontitis and prostate diseases.